Hospital safety culture and sexual harassment on turnover intention of nurses in Upper East region, Ghana - Tabase, Charles Lwanga Moandiyiem (University of Cape Coast, 2023)
The study investigated the relationship between safety culture, sexual harassment, and turnover intention among nurses and midwives in Ghana's Upper East Region. Four research questions guided the study, which collected data from 812 nurses/midwives using a cross-sectional design. The Upper East Region was selected using the purposive sampling method, and the census method was used to collect data from nurses and midwives. A questionnaire from pre-existing instruments was used to collect data, which were analysed using frequencies, percentages, and logistic regression. The results indicated a medium level of perceived safety culture among nurses in the Upper East Region, with a prevalence of 63.1%. There is an unacceptable level of sexual harassment reported by nurses/midwives, with 30.7% reporting general sexual harassment, 27.3% reporting harassment based on gender, 50.9% unwanted sexual advances, and 49.8% reporting sexual coercion at work. Moreover, as high as 59.4% of these nurses/midwives declared their intention of leaving the profession or Upper East Region very shortly. Furthermore, turnover intention among the nurses/midwives was determined by the organisational safety culture, their level of working experience, sexual harassment, and gender, with the females more harassed than the males. Therefore, with the high levels of workplace sexual harassment, many nurses/midwives may leave work soon, compromising quality healthcare delivery in the area. Thus, there is an urgent need to re-examine the organisational safety culture to address workplace sexual harassment against nurses/midwives, especially females.
xii,163p:,ill